Status Keberlanjutan Wilayah Berbasis Peternakan Sapi Potong Terpadu di Kabupaten Lima Puluh Kota – Sumatera Barat - Suyitman Suyitman; S.H Sutjahjo; A Djulardi (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2012)
The aim of this research is to analyze the sustainability status by measuring sustainability index of Kabupaten Lima Puluh Kota area in five dimensions of sustainability. The research methods was Multidimensional Scaling (MDS) that called Rap-BANGKAPET. Rap-BANGKAPET supported with Leverage and Monte Carlo analysis to determine attributes that affects the index and status of sustainability. Sustainability analysis resulted ecological dimension was less sustained (46.50%), economical dimension was sustained (69.53%), social and cultural dimension was sustained enough (55.14%), infrastructure and technology dimension was less sustained (45.48%), legal and institutional dimension less sustained (47.46%).  From 73 attributes which analysed, only 24 attributes will need to settle immediately because could affects sustainability index sensitively, proven with minimum error at 95% confidence level. Prospective analysis is needed to build scenarios to increase sustainability index and sustainability status in future. There is progressive-optimistic scenarios with overall improvement at sensitive attributes could increase sustainability status of  area.